Faktor-Faktor Yang Berpengaruh Terhadap Kepatuhan Pembayaran Pajak - N. Purnomolastu (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
Tax is Indonesian country main source which should be increased in income. In order to increase the income in tax field, so the effort done by the government is by improving taxpayer obedience. The taxpayer obedience about tax payment needs to be improved continually, remembering the comparation ratio of tax income total and gross domestic product that is also called as tax ratio is still low. Indonesian Tax Ratio about 12% is still far from the hoped. The efforts for improving taxpayer obedience continue to be done by the government, i.e. through several ways. They are improving tax socialization by various kinds of campaign, improving service toward taxpayer through prime service and law enforcementtoward taxpayer through taxation sanctions. In this research, the writer expresses the socialization factor influences, law service and enforcement toward the obedience level of taxpayer payment. The obedience itself can characterize as formal, i.e. the obedience in delivering reports and material obedience, it is the paid nominal amounts.